Perilaku pada Mahasiswa yang Memiliki People pleasing - Rafifah Nabila; Endang Setianingsih (Indo Publishing, 2026)
This community service program aims to explore and understand the phenomenon of people-pleasing behavior among university students. People-pleasing is defined as a behavioral pattern focused on fulfilling others' needs and expectations while neglecting personal needs, often driven by fear of rejection and a strong need for social validation . This behavior has been linked to various negative psychological outcomes, including emotional exhaustion, stress, and decreased self-esteem . The program employed a qualitative phenomenological approach to gain an in-depth understanding of students' subjective experiences. A total of seven students actively involved in student organizations participated in the program, which consisted of three main phases: pre-intervention assessment through in-depth interviews, intervention implementation including psychoeducational sessions and assertiveness training, and post-intervention evaluation through reflective interviews . The findings reveal that people-pleasing behavior among students arises from a strong need for external validation, fear of rejection, and social pressures, including complex organizational roles. Participants experienced significant psychological impacts, such as emotional exhaustion, stress, guilt, and loss of personal identity. Nonetheless, several students have started to develop awareness of the importance of setting personal boundaries and implementing strategies to maintain their psychological well-being, including learning to say no, setting priorities, and building healthier social relationships . This program contributes to the development of evidence-based mental health interventions in higher education settings and highlights the importance of addressing maladaptive interpersonal patterns early in young adulthood.